Adoption of Wxmaxima software in the classroom: effect on students' motivation and learning of mathematics - Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani; Abu Bakar, Kamariah; Wong, Su Luan (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
This study investigates the effect of usage of an open-source software, WxMaxima, on students’ achievement in calculus scores and their motivation towards learning mathematics using the software. The study involved of 62 secondary school students (32 in the treatment group, 30 in the control group) in a Malaysian school. ANCOVA analysis showed that that the group with access to WxMaxima achieved significantly better test scores as compared with the group which followed the traditional teaching method. Students in the treatment group were also better motivated towards learning mathematics; they were more attentive and showed more confidence in learning calculus. However, there was no significant difference in terms of ‘satisfaction’ in learning mathematics between the two groups. The results from this study suggest that the integration of computer technology in the teaching and learning of calculus and of mathematics in general was generally beneficial.